2016
DOI: 10.1097/iae.0000000000001015
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and Functional Outcomes of Symptomatic Idiopathic Vitreomacular Traction

Abstract: Spontaneous resolution of VMT occurred in 21.4% (36 of 168) of eyes after a mean follow-up of 11.4 ± 12.6 months. An unfavorable anatomical outcome occurred in 7.7% (13 of 168) of eyes. The baseline SD-OCT grade may predict the progression to full-thickness macular hole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 30 publications
0
11
3
Order By: Relevance
“…Regarding intraretinal anomalies, the analysis of the 31 eyes with VMT in our series showed that 71.4% (5/7) of the eyes with isolated foveal surface distortion at baseline developed an MH, as compared to only 25% (6/24) of those with associated intraretinal anomalies at baseline, without reaching significance ( p = 0.07). This result could appear paradoxical and in contrast with other reports, where the presence of a foveal elevation has been reported to confer a higher risk of developing MH both in fellow eyes of eyes with MH and in eyes with VMT [10, 16]. Several hypotheses could be proposed to explain this difference.…”
Section: Discussioncontrasting
confidence: 68%
“…Regarding intraretinal anomalies, the analysis of the 31 eyes with VMT in our series showed that 71.4% (5/7) of the eyes with isolated foveal surface distortion at baseline developed an MH, as compared to only 25% (6/24) of those with associated intraretinal anomalies at baseline, without reaching significance ( p = 0.07). This result could appear paradoxical and in contrast with other reports, where the presence of a foveal elevation has been reported to confer a higher risk of developing MH both in fellow eyes of eyes with MH and in eyes with VMT [10, 16]. Several hypotheses could be proposed to explain this difference.…”
Section: Discussioncontrasting
confidence: 68%
“…Over the past two decades, the literatures [3,12,22,[26][27][28][29][30][31][32] available on the incidence of adverse retinal disorders such as macular hole that are associated with VMA has been limited. Furthermore, the findings are quite variable due to differences in a range of factors; these include the study design (cross sectional or longitudinal; prospective or retrospective), the diagnostic tools used (ultrasound, OCT, etc) and the different criteria utilized to define the classification and diagnosis of VMA or vitreomacular separation (with or without acute symptoms) [2-4, 8, 12, 22, 27].…”
Section: Macular Holesmentioning
confidence: 99%
“…Furthermore, the findings are quite variable due to differences in a range of factors; these include the study design (cross sectional or longitudinal; prospective or retrospective), the diagnostic tools used (ultrasound, OCT, etc) and the different criteria utilized to define the classification and diagnosis of VMA or vitreomacular separation (with or without acute symptoms) [2-4, 8, 12, 22, 27]. Additionally, a recent retrospective multicenter study [27] has reported that full thickness macular holes occurred in 7 out of 168 eyes (4.2%) with vitreomacular traction. This differs to some extent to the present retrospective study in which the incidence of full thickness macular holes was 6.5% (8 out of 124 eyes).…”
Section: Macular Holesmentioning
confidence: 99%
“…2,5 Although there are several reports on the natural course of VMT, the frequency of spontaneous release varies widely in the literature. 6,7 Pars plana vitrectomy (PPV) is still the treatment of choice for eyes with broad vitreomacular adhesions and significant ERM component. 2,4 Although the success rate of PPV as a treatment for VMT is high, it carries the risk of cataract formation, endophthalmitis, retinal tear, or detachment.…”
Section: Introductionmentioning
confidence: 99%